Gentamicin treatment in exercised mdx mice: Identification of dystrophin-sensitive pathways and evaluation of efficacy in work-loaded dystrophic muscle - Annamaria De Luca; Beatrice Nico; Jean-François Rolland; Anna Cozzoli; Rosa Burdi; Domenica Mangieri; Viviana Giannuzzi; Antonella Liantonio; Valentina Cippone; Michela De Bellis; Grazia Paola Nicchia; Giulia Maria Camerino; et al. (Neurobiology of Disease, 2008)
Aminoglycosides force read through of premature stop codon mutations and introduce new mutation-specific gene-corrective strategies in Duchenne muscular dystrophy. A chronic treatment with gentamicin (32 mg/kg/daily i.p., 8–12 weeks) was performed in exercised mdx mice with the dual aim to clarify the dependence on dystrophin of the functional, biochemical and histological alterations present in dystrophic muscle and to verify the long term efficiency of small molecule gene-corrective strategies in work-loaded dystrophic muscle. The treatment counteracted the exercise-induced impairment of in vivo forelimb strength after 6–8 weeks. We observed an increase in dystrophin expression level in all the fibers, although lower than that observed in normal fibers, and found a concomitant recovery of aquaporin-4 at sarcolemma. A significant reduction in centronucleated fibers, in the area of necrosis and in the percentage of nuclear factor-kB-positive nuclei was observed in gastrocnemious muscle of treated animals. Plasma creatine kinase was reduced by 70%. Ex vivo, gentamicin restored membrane ionic conductance in mdx diaphragm and limb muscle fibers. No effects were observed on the altered calcium homeostasis and sarcolemmal calcium permeability, detected by electrophysiological and microspectrofluorimetric approaches. Thus, the maintenance of a partial level of dystrophin is sufficient to reinforce sarcolemmal stability, reducing leakiness, inflammation and fiber damage, while correction of altered calcium homeostasis needs greater expression of dystrophin or direct interventions on the channels involved.